2022
DOI: 10.1111/head.14278
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of manual therapy in the treatment of cervicogenic headache: A systematic review

Abstract: Objective:The aim of this study was to identify the manual therapy (MT) methods and techniques that have been evaluated for the treatment of cervicogenic headache (CH) and their effectiveness.Background: MT seems to be one of the options with the greatest potential for the treatment of CH, but the techniques to be applied are varied and there is no consensus on which are the most indicated. Methods: A systematic search in Scopus, Medline, PubMed, Cinahl, PEDro, and Web of Science with the terms: secondary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Interestingly, headaches can emerge from cervical discomfort even in asymptomatic individuals, particularly when cervical muscles like the levator scapulae, sternocleidomastoid (SCM), trapezius, and paraspinal muscles are weakened or fatigued. This connection between headaches and neck muscle issues underscores the importance of addressing these factors for effective treatment (8,9). Cervical muscles with structural and functional anomalies are less capable of generating and maintaining the necessary torque for optimal functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, headaches can emerge from cervical discomfort even in asymptomatic individuals, particularly when cervical muscles like the levator scapulae, sternocleidomastoid (SCM), trapezius, and paraspinal muscles are weakened or fatigued. This connection between headaches and neck muscle issues underscores the importance of addressing these factors for effective treatment (8,9). Cervical muscles with structural and functional anomalies are less capable of generating and maintaining the necessary torque for optimal functioning.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review have demonstrated the efficacy of the Mulligan maneuvre for CEH on clinical pain scales and cervical range of motion after treatment 12 . However, they do not take into account the fact that chronic pain results in feelings of anxiety or depression in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cervicogenic headache (CeH) is a type of referred pain which originates from cervical structures innervated by C1–C3 spinal afferents ( Bogduk and Govind, 2009 ). Both anatomical lesions as well as musculoskeletal dysfunctions of the upper-cervical spine could be sources of CeH ( Bogduk and Govind, 2009 ; Núñez-Cabaleiro and Leirós-Rodríguez, 2022 ). Such upper-cervical musculoskeletal dysfunctions are commonly targeted by physiotherapists, manual therapists, chiropractors, and osteopaths ( Biondi, 2005 ; Bryans et al, 2011 ; Luedtke et al, 2016a , Luedtke et al, 2016b ; Núñez-Cabaleiro and Leirós-Rodríguez, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both anatomical lesions as well as musculoskeletal dysfunctions of the upper-cervical spine could be sources of CeH ( Bogduk and Govind, 2009 ; Núñez-Cabaleiro and Leirós-Rodríguez, 2022 ). Such upper-cervical musculoskeletal dysfunctions are commonly targeted by physiotherapists, manual therapists, chiropractors, and osteopaths ( Biondi, 2005 ; Bryans et al, 2011 ; Luedtke et al, 2016a , Luedtke et al, 2016b ; Núñez-Cabaleiro and Leirós-Rodríguez, 2022 ). Nevertheless, despite the well-known pathophysiology of CeH, the number of non-responders amounts to 25%, and self-reported effectiveness of manual therapy is only rated as 36% ( Ossendorf et al, 2009 ; Liebert et al, 2013 ; Moore et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%